STRATEGI PENGEMBANGAN MANGGIS RATU TEMBILAHAN DI KECAMATAN TEMBILAHAN HULU - Partini Partini; Tomy Prasetia (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2021)
Mangosteen is fruit commodity that was sold in the form of fresh fruit and could be processed as herbal medicine and cosmetic. Market demand of mangosteen increase both of in the country and export market. Sub district of Tembilahan have variety of mangosteen that superior quality it’s name mangosteen of Ratu Tembilahan. The aims of this study to (1) know potential development of mangosteen in Sub district of Tembilahan Hulu, (2) determine strategies of mangosteen development in Sub district of Tembilahan Hulu. The data analysis was done using the Location Quotient (LQ) dan SWOT analysis. The results of the study were (1) Mangosteen was superior commodity in Sub district of Tembilahan Hulu (LQ= 1.76), (2) alternative strategies for mangosteen develepment were (a) replanting for old mangosteen, (b) Sertification of mother trees for sources of seed that used by local farmers, (c) improve management of mangosteen farming, (d) training of mangosteen processing to be derivative products. Manggis merupakan komoditas buah yang dikonsumsi sebagai buah segar maupun diolah menjadi obat herbal dan kosmetik. Permintaan manggis mengalami peningkatan baik untuk pasar dalam negeri maupun pasar ekspor. Kecamatan Tembilahan Hulu memiliki varietas manggis yang unggul bernama manggis Ratu Tembilahan. Tujuan penelitian ini adalah (1) untuk mengetahui potensi pengembangan manggis Ratu Tembilahan; (2) menentukan strategi pengembangan manggis Ratu Tembilahan. Metode analisis data menggunakan analisis LQ dan analisis SWOT. Hasil penelitian menunjukkan bahwa (1) Manggis merupakan komoditas basis di Kecamatan Tembilahan Hulu dengan nilai LQ= 1,76, (2) alternatif strategi pengembangan manggis Tembilahan Hulu adalah (a) Peremajaan tanaman manggis tua, (b) Sertifikasi pohon induk sebagai sumber bibit para penangkar bibit lokal, (c) Peningkatan pengelolaan usaha tani manggis, (d) Pelatihan pembuatan produk olahan manggis.